The Value of Art for Life: Critical Reflections on Creativity and the Art of Living Well - Jill Marsden (Philosophies, 2025)
The contribution that arts can make to our health and wellbeing is widely acknowledged in public discourse, with the concept of ‘creative health’ having come to prominence in the UK in the last ten years. This paper asks about the kinds of values at play in contemporary appeals to creativity by exploring the value of art for life from a philosophical perspective. Drawing on Pierre Hadot’s influential work on the ancient philosophical practice of the ‘art of living’, it goes on to consider how aesthetic perception of the world functions as a kind of model for philosophical perception. Inflecting these ideas with Friedrich Nietzsche’s genealogical critique of values, the paper examines the role of art and philosophy in relation to luxury and need, and to fundamental conditions of life enhancement. Building on this distinctive application of Nietzsche’s genealogy, it develops the question of how to assess the value of art for life outside the current neoliberal narratives of wellbeing and the creative industries. In its focus on values rather than ideals, the paper makes an original contribution to current thinking and practice in creative health.